Mechanochemical control of graphene etching along zigzag and armchair edge directions - Yilong Jiang; Chuan Tang; Chao Chen; Yangqin Liu; Yang Wang; Seong H. Kim; Junhui Sun; Linmao Qian; Lei Chen (Friction)
The atomic edge structure of graphene governs its unique electronic properties with applications in nanoscale electronics and optoelectronics. To fully realize its potential, it is critical to develop a precision etching process producing graphene edges along desired directions. Here, we present a novel approach utilizing scanning probe lithography (SPL) facilitated by a mechanochemical atomic attrition process. This technique enables the fabrication of nanopatterns in single-layer graphene from graphene edges, precisely along the crystallographic orientation of zigzag (ZZ) and armchair (AC) edges, without inducing mechanical damage to the surrounding area. Density functional theory (DFT) calculations revealed that the dissociation of C‒C bonds by the SPL probe is mediated by the formation of interfacial bridge bonds between the graphene edge and the reactive silica surface. This SPL-based mechanochemical etching method enables the construction of various nanodevice structures with specific edge orientations, which allows the exploitation of their electronic properties.